Optimalisasi Dashboard Pemesanan Makanan Online Menggunakan Looker dan JavaScript - Angginy Akhirunisa Siregar; Citra; Khairun Nadiah; Hermawan Syahputra; Fanny Rahmadani (Masyarakat Ekonomi Syariah Bogor, 2024)
Advances in information technology have enabled rapid development in internet-based services, including online food ordering applications. This growth demands efficient data management and analysis systems to improve user experience and operational performance. This research focuses on developing an optimal online food ordering dashboard using Looker and JavaScript. Research methods include needs identification, literature study, needs analysis, design, and implementation. The research results show that the dashboard developed is able to manage and analyze order data effectively, identify trends, predict customer needs, and increase operational efficiency. This dashboard visualizes important information such as number of orders based on age, gender, income, as well as customer behavior analysis. In doing so, service providers can gain better insight into consumer behavior and ordering trends, supporting more informed and strategic decision making. The results of this study contribute to the literature on the use of data visualization technologies in the online food service sector.